Levels of paraoxonase and arylesterase activities and malondialdehyde in workers exposed to ionizing radiation - Serhatlioglu, S; Gursu, MF; Gulcu, F; Canatan, H; Godekmerdan, A (John Wiley & Sons Ltd, 2003)
We examined levels of malondialdehyde (MDA) (an end-product of lipid peroxidation) and paraoxonase (PON1) (an antioxidant enzyme) activity and PON1 phenotypes in people who were exposed to ionizing radiation for different time periods and doses. A total of 78 individuals (mean age 34 7 years) were included in the study. Fifty-one of them were radiology workers whereas the control group was composed of 27 healthy volunteers who had never worked in a radiology-related job. Paraoxon was used as substrate for measurement of PON1 activity levels (basal and NaCl-stimulated). Phenylacetate was used as substrate for measurement of arylesterase activity levels. Cumulative levels of serum NaCl-stimulated PON1/arylesterase activities were utilized for phenotypic differentiation. In radiology workers, three different phenotypes were determined based on paraoxonase/arylesterase ratio. The ratios were 1.09 +/- 0.30 for AA (homozygote low activity); 2.91 +/- 1.07 for AB (heterozygote activity) and 4.97 +/- 1.21 for BB (homozygote high activity). There was a statistically meaningful negative correlation between serum MDA levels and PON1 activity levels in all phenotypes (p < 0.05). PON1 activity levels were found to be 25-35% lower in people who were exposed to long-term (>5 years) radiation compared to controls. There was no statistically significant correlation between serum arylesterase activity and MDA levels in these subjects (r = -0.185, p > 0.05). PON1 activity levels were decreased whereas serum MDA levels were increased in individuals exposed to radiation for a long period. PON phenotypes of people employed in jobs which expose them to radiation should be determined and based on these findings they should be advised to avoid risk factors inducing oxidative stress, such as smoking, and to consume foods rich in vitamins and trace elements to increase their antioxidant capacity. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: ionizing radiation; paraoxonase; arylesterase; malondialdehyde